The study of Histone Deacetylases Immunoexpression in relation to Regulating Vascular Endothelial Growth Factor (VEGF) Implicated in Malignant Progression of Colorectal cancer - Qaddoori, Yasir B.; AL‑Khafaji, Ahmed S.K.; Khashman, Basim M.; Abdul Ghafour, Kifah H. (Iraqi Journal of Science, 2025)
Colorectal cancer is a malignant condition that can arise from multiple causative factors. It ranks second, behind lung cancer, as a leading cause of cancer-related deaths worldwide. Extensive research has been conducted to unravel the genetic underpinnings and molecular mechanisms underlying the development of colorectal cancer (CRC). However, epigenetic modifications of histones at the DNA level have become significantly involved in several malignant diseases such as CRC. Hence, this research sought to assess, for the first time locally, the immunoexpression of HDAC-1 and 3 in a group of colorectal patients. Additionally, we explored potential correlations between the expression of HDAC-1, 3 and VEGF. This retrospective study encompassed the analysis of 95 paraffin-embedded tissue samples from CRC cases. Participants in the research varied in age from 22 to 79 years, consisting of 60 males and 35 females. The study findings revealed a noteworthy correlation between VEGF expression and the patients' sex (p = 0.005, rho = 0.289). Intriguingly, the analysed data demonstrated a significant correlation between VEGF expression and the cytoplasmic localization of HDAC3 in colorectal cancer tissues (p < 0.001, rho = 0.476). However, the expression of VEGF showed a negative and statistically significant correlation with both HDAC3 expression (p = 0.02, rho = -0.243) and the cytoplasmic localization of HDAC1 (p = 0.02, rho = -0.305). The demonstrated negative regulatory relationship between HDAC3 and VEGF suggests this correlation could potentially be leveraged in both disease prognosis and treatment. Targeting the negative regulatory interaction between HDAC3 and VEGF may provide promising opportunities in both prognostic assessment and therapeutic strategies. This highlights the potential for developing targeted strategies that capitalize on the interplay between angiogenesis and epigenetic regulation.